Convergent synthesis of the tetrasaccharide repeating unit of the cell wall lipopolysaccharide of Escherichia coli O40 - Sau, Abhijit; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2012)
A tetrasaccharide repeating unit corresponding to the cell-wall lipopolysaccharide of E. coli O40 was synthesized by using a convergent block glycosylation strategy. A disaccharide donor was coupled to a disaccharide acceptor by a stereoselective glycosylation. A 2-aminoethyl linker was chosen as the anomeric protecting group at the reducing end of the tetrasaccharide. All glycosylation steps are significantly high yielding and stereoselective.
Keywords: Escherichia coli; glycosylation; lipopolysaccharide; O-antigen; tetrasaccharide